AN ANALYSIS ON THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITY, AND FIRM SIZE ON FIRM VALUE WITH MANAGERIAL OWNERSHIP AS MODERATING VARIABLE IN OPEN MINING COMPANIES - herawati, christine (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to examine and to analyze the influence of CSR, profitability, and firm size on firm value in mining companies listed in BEI (Indonesia Stock Exchange) simultaneously and partially and to examine and to analyze whether managerial ownership could moderate the influence of CSR, profitability, and firm Size on firm value in mining companies listed in IDX